Good governance in the Middle East oil monarchies - Najem, Tom; Hetherington, Martin (Durham modern Middle East and Islamic world series, 2003)
The concept of 'good governance' is of increasing importance, and is used by international organizations to ensure reasonable conformity to high standards in states which participate in the global trading regime and other international activities. This book examines the concept of good governance and how it is applied in the states of the Gulf Co-operation Council. These states are particularly important because of their strategic location and massive oil wealth. Moreover, as monarchies, in most cases without powerful democratic representative bodies, and as Islamic countries, with a differ.